Stakeholder Roles in Strengthening Religious Moderation: A Case Study of Socio-Religious Conflict in Mesanggok Village, Gerung Subdistrict, West Lombok Regency - Abdurrahman; Fibrian Khotmul Aula Putra (Journal of Nahdlatul Ulama Studies, 2025)
Religious moderation denotes a perspective, disposition, and practice of religiosity that foregrounds justice, balance, respect for human dignity, and commitment to the national civic compact. Yet in rural communities with entrenched religious traditions, the entry of preaching currents that label local practices as bid‘ah may generate delegitimation, polarization, and conflict escalation. This article addresses three questions: (1) how the chronology and dynamics of socio-religious conflict escalation unfolded in Mesanggok Village, Gerung Subdistrict, West Lombok; (2) how stakeholders (village government, police, the Indonesian Ulama Council/MUI, the Office of Religious Affairs/KUA, the Religious Harmony Forum/FKUB, Lakpesdam NU, religious counsellors, faith-based organizations, youth, and academics) contributed to strengthening religious moderation and post-conflict recovery; and (3) how cross-actor musyawarah (deliberative consultation) produced consensus and programmes to prevent recurrent conflict. Using a qualitative case-study design, data were collected through observation, in-depth interviews, document review, community deliberations (sarasehan), and focus group discussions, and were analysed thematically and iteratively through coding and case-narrative construction with source and method triangulation. The findings show that stakeholder collaboration operated through four stages: (1) de-escalation and security protection, (2) mediated dialogue and norm clarification, (3) the formation of community consensus and rules of engagement, and (4) the institutionalisation of inclusive religious programmes (routine cross-group study circles) that frame differences as manageable khilāfiyah (legitimate interpretive disagreement) rather than identity-threatening disputes. In conclusion, the Mesanggok conflict emerged not merely from theological disagreement but from struggles over legitimacy and the delegitimation of local religious traditions. Recovery proved most effective when religious moderation was enacted through collaborative, deliberative governance that distributed stakeholder roles protection, mediation, norm production, and programme institutionalization in a synergistic and sustained manner. The study recommends: establishing inclusive village-level deliberation protocols; strengthening public literacy on ikhtilāf and the ethics of da‘wah through MUI, KUA, Lakpesdam NU, religious counsellors; developing mediation-oriented community policing; and extending cross-group programmes to the hamlet/RT level to prevent renewed escalation.